2022
DOI: 10.1177/23259671221103845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Joint Space Width on Lateral Meniscal Allograft Transplantation: Outcomes at Midterm Follow-up

Abstract: Background: It remains unclear whether lateral joint space narrowing without severe cartilage loss before meniscal allograft transplantation (MAT) affects clinical outcomes and graft extrusion. Hypothesis: Patients with greater preoperative joint space narrowing would show more graft extrusion, more osteoarthritis progression, and worse clinical outcomes than would those with less narrowing. Study Design: Case-control study; Level of evidence, 3. Methods: We retrospectively evaluated 61 patients who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…According to previous studies, a poor cartilage status is one of the causes of failure after MAT [4, 18, 32]. In this study, the majority of patients in the lateral MAT group had a high ICRS grade.…”
Section: Discussionsupporting
confidence: 53%
“…According to previous studies, a poor cartilage status is one of the causes of failure after MAT [4, 18, 32]. In this study, the majority of patients in the lateral MAT group had a high ICRS grade.…”
Section: Discussionsupporting
confidence: 53%
“…We did not apply universal classification such as Kellgren-Lawrence grade to determine joint space narrowing of the lateral edge [ 39 , 40 ]. Lee et al [ 24 ] revealed that joint cartilage is relatively well maintained when only the lateral edge, not the joint obliteration, is narrow in a considerable number of patients. They showed no significant differences in the ratio of lesions ≥ modified Outerbridge grade 3 between less and moderate joint space narrowing groups.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements were performed on a picture archiving and communication system (PACS) workstation (Centricity RA 1000; GE Healthcare, Chicago, IL, USA). The absolute JSW was calculated from the lateral edge of the femoral condyle to the lateral edge of the tibial plateau [ 22 , 23 , 24 ] ( Figure 5 ). Our previous study proved that only the lateral edge was observed to be significantly reduced without whole joint obliteration at the time of lateral meniscal allograft transplantation [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations